JMD238 : Computer aided design introductory / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course provides a comprehensive introduction to computer-aided design software. Students will learn to utilize the software by tracing and creating basic designs followed by the presentation. The course is designed to help students to learn about dimensioning, labeling, producing artworks, and rendering. Students will be equipped with the skills to produce a layout for design presentations with text, graphics, and photos.